Dyadic construction of dementia: meta-ethnography and behaviour-process synthesis - Bosco, Alessandro (Taylor & Francis, 2018)
Objectives: Positive identity in people with dementia is maintained when there is good interaction with family caregivers. However, research on the experiences of dyadic interaction in dementia care is still limited. For this reason, we aimed to systematically review the dyadic experience of dementia caring. Method: Studies were identified through searching five databases: MedLine, EMBASE, PsycInfo, ASSIA, and CINAHL. Eligible studies employed qualitative or mixed method design, reported the experience of dyads of dementia with no comorbid organic or psychiatric disorders. No restrictions were made on language or year of publication, nor on sex or age of participants. The quality appraisal of studies was conducted by two researchers independently. We used meta-ethnography to synthesise data and developed a behavioural model to explain dyadic interaction. Results: A total of 17 studies were included in the review. The meta-ethnography generated two third-order constructs: Personal orientation and noises. When both people with dementia and their carers opt for dyadic oriented goals, their behavioural responses are likely to promote positive interaction. When only one partner opts for dyadic goals, the stress posed by the context may affect the interaction because of no perceived shared understanding of the situation. Conclusion: Our findings suggest that unequal power distribution within dementia dyads, can cause significant stress especially when coping strategies are impaired. Implications are found for family carers, people with dementia, and health professionals as the model we derived enhances the understanding of dyadic dynamics to care.